A Systematic Review of the Virtues and Vices of Exit Exams in Higher Education - Teshome, Samson Worku (International Journal of Education, Culture, and Society, 2025)
Exit exams in higher education have become central tools for assessing students' readiness for professional roles or advanced academic pursuits, aiming to uphold accountability, standardization, and quality assurance across educational systems. Designed to evaluate mastery of discipline-specific knowledge, skills, and competencies, their implementation has sparked ongoing debate about their effectiveness and equity. This systematic literature review synthesizes findings from 33 peer-reviewed studies to examine both the advantages and challenges associated with exit exams. The review identifies that exit exams enhance transparency, promote comparability, and align academic outcomes with labor market expectations. However, they also present significant drawbacks, including the risk of over-standardization, elevated psychological stress, and reinforcement of systemic biases. Marginalized student populations are often disproportionately affected, as high-stakes testing can deepen existing educational inequalities and promote surface-level learning due to a "teaching to the test" approach. Technical limitations in digital exam delivery and uneven access to preparatory resources further undermine equitable assessment. Nevertheless, exit exams can offer constructive feedback to both learners and institutions, supporting curricular refinement and improving graduate employability. The review advocates for a more balanced and inclusive assessment model that integrates formative evaluations, leverages flexible technological platforms, and considers student mental well-being. By aligning exit exam practices with holistic educational goals and incorporating qualitative metrics, institutions can develop fairer, more effective frameworks that serve diverse student populations and drive continuous improvement in higher education.